2015
DOI: 10.3389/fpls.2015.00861
|View full text |Cite
|
Sign up to set email alerts
|

TOR-inhibitor insensitive-1 (TRIN1) regulates cotyledons greening in Arabidopsis

Abstract: Target of Rapamycin (TOR) is an eukaryotic protein kinase and evolutionally conserved from the last eukaryotic common ancestor (LECA) to humans. The growing evidences have shown that TOR signaling acts as a central controller of cell growth and development. The downstream effectors of TOR have been well-identified in yeast and animals by using the immunosuppression agent rapamycin. However, less is known about TOR in plants. This is largely due to the fact that plants are insensitive to rapamycin. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 77 publications
4
64
0
Order By: Relevance
“…These genes were also repressed by ABA but strongly induced by the application of brassinolide. This is consistent with the inhibitory effects of ABA on the growth-promoting hormones like brassinosteroid and with the role of TOR in brassinosteroid (Zhang et al, 2009, 2016) and ABA signaling (Kravchenko et al, 2015; Li et al, 2015), which could result in TOR inhibition. As reported earlier by Pal et al (2013) we found diverse and uncoordinated responses to variations in sugar supply for nuclear genes coding for pRPS while their expression was repressed by nitrogen starvation as observed in Chlamydomonas (Schmollinger et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These genes were also repressed by ABA but strongly induced by the application of brassinolide. This is consistent with the inhibitory effects of ABA on the growth-promoting hormones like brassinosteroid and with the role of TOR in brassinosteroid (Zhang et al, 2009, 2016) and ABA signaling (Kravchenko et al, 2015; Li et al, 2015), which could result in TOR inhibition. As reported earlier by Pal et al (2013) we found diverse and uncoordinated responses to variations in sugar supply for nuclear genes coding for pRPS while their expression was repressed by nitrogen starvation as observed in Chlamydomonas (Schmollinger et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…About half of the plastid small ribosome subunit (30S) proteins and most of the large subunit (50S) proteins are encoded by the nuclear genome (Yamaguchi and Subramanian, 2000). TOR silencing (Deprost et al, 2007; Xiong and Sheen, 2012; Caldana et al, 2013), inhibition by rapamycin (Sormani et al, 2007; Ren et al, 2011) or by AZD-8055 (Montané and Menand, 2013; Li et al, 2015) as well as mutations affecting the TORC1 complex (Moreau et al, 2012; Kravchenko et al, 2015) consistently result in leaf chlorosis and yellowing. We show here that TOR inhibition results in a coordinated decrease in pRP expression, at the level of protein abundance but also at the total and translated mRNA levels, which could explain these chlorotic phenotypes ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that AZD can induce growth retardation of cotton seedlings, and these effects were dose-dependent (as indicated by root length and fresh weight). This suggests that AZD based approach can be used to probe TOR signaling in cotton similar to other plants89.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, we also found the altered expression profiles of auxin and abscisic acid (ABA) related genes under TOR inhibition in cotton; these observations are highly consistent with similar treatments in Arabidopsis 11 (Supplementary Table 3). As the crosstalk between TOR and ABA or auxin signaling pathways have already been previously investigated92930, we focused on JA signaling pathway for further investigation. The expression levels of some randomly-selected genes were verified using QRT-PCR, and the results were consistent with the RNA-Seq analysis (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation